Retrospective analysis of tubectomy beneficiaries in rural area (PHC KINAYE): one year record based study - Chaudhary, Preeti; Kadeangadi, Deepti M.; Arora, Ipsa (International Journal Of Community Medicine And Public Health, 2016)
Background: Population explosion has become a major concern in India. As per NFHS- IV report in Karnataka, 52.8% adopted the female sterilization other methods like male sterilization 0.0%, Intrauterine devices 0.6% and pills users were 0.3%, condom 0.6% in rural areas. The study of female sterilization as the method of choice in rural field practice area of Kinaye, PHC, Belagavi was done for a period of one year. Methods: Retrospective Data Analysis of 200 women undergoing sterilization at PHC, Kinaye in Belagavi district of Karnataka state from 1st April 2015 to 31st March 2015 was done. The variables considered were age of beneficiary, husband’s age, religion, educational status of beneficiary and of husband, total number of living children, number of sons, number of daughters, socio-economic status and their motivators etc. Results: Out of 200 women adopting sterilization, 57.0% (114) were from the age group of 25-29 years. The maximum percentage (81.0%) of their husbands were from the age group of 30-34 years. 95.0% of the participants were Hindus. Nearly two thirds of the beneficiaries had attained secondary education (61.0%). 60.0% of the beneficiaries were belonging to the BPL group (Below Poverty Line). 55.5% of the participants had two living children. 58.0% of them had one male child, 33.5% of them had two male children, 51.0% of them had one female child. 53.0% of the participants were motivated by ASHA workers. Conclusions: More than half of the tubectomy beneficiaries belonged to the age group of 24-29 years. Of them around two third belonged to the BPL group and more than half were motivated by the ASHA workers. More than half of the women undergoing tubectomy were having two live children, around three fifth of them were having one male child and around half of them were having one female child.